존 클레어의 본향 찾기의 시학 - 유선무 (19세기 영어권 문학, 2018)
This paper examines John Clare’s sense of place, refuting the traditional reading of Clare as a Schillerian “naive poet” whose descriptive poetics unselfconsciously erases the distance between the poetic subject and nature. Far from considering nature as an original, stable site of unity and identity, Clare looks to nature as a place of difference. Clare describes nature not as a comfortable place of belonging but as a discontinuous place, where both human and non-human subjects are exposed to the elemental and the hostile. Nevertheless, his detailed observation of non-human subjects helps him learn their art of dwelling that transforms displacement into a sense of belonging. He practices this art of dwelling in order to cope with displaced modern existence so that human subjects can resist the alienating power of modernism without being rigid or exclusive to others. His unique notion of home destabilizes the rigid boundary between the familiar and the strange and between presence and absence. Eventually, he presents the idea that we are “homeless at home,” which he regards as a condition for happy coexistence on earth. This notion of “being homeless at home” allows us to reflect on our contemporary situation by opening our home-place to the unexpected and the uncanny.
Keywords: 존 클레어; 순진한 시인; 본향; 장소감; 이주; 본향에서조차 본향상실; John Clare; naive poe; home; sense of place; displacement; homeless at home